Domestic Debt, Private Sector Credit and Economic Growth in Sub‐Saharan Africa. (4th January 2014) - Mbate, Michael
Abstract: Exercising fiscal prudence in periods of deteriorating fiscal balance requires sound policies which promote debt sustainability. This paper estimates a dynamic cross‐country model and investigates the impact of domestic debt on economic growth and private sector credit in a panel of 21 sub‐Saharan African (SSA) countries over the period 1985 to 2010. System‐GMM results reveal a non‐linear relationship between domestic debt and economic growth, characterized by a maximum turning point of 11.4 per cent of GDP. In addition, domestic debt is found to crowd out private sector credit by an elasticity of negative 0.3 per cent of GDP, deterring capital accumulation and private sector growth. These findings underscore the need for effective debt management strategies which incorporate debt ceiling to limit domestic indebtedness, as well as the design of financial policies which enhance credit availability, promote fiscal discipline and deepen domestic debt markets on the continent.